EL SUEÑO DE LOS AFRANCESADOS PRODUCE MONSTRUOS. LE FLAGELLANT DE SÉVILLE DE PAUL MORAND - Illanes Ortega, Inmaculada (Anales de Filología Francesa, 2008)
Paul Morand considers history an important clue to understand a nation’s character. In Le flagellant de Séville, he uses Goya’s colours to paint Spanish soul by narrating an individual tragedy inscribed in the collective dramatic events of Spanish history between 1808 and 1815, when the destinies of Spain and France converged once again. In his novel, Morand offers a lucid vision of Spanish people and history, which should lead to a more general